2017
DOI: 10.1080/00365513.2017.1328740
|View full text |Cite
|
Sign up to set email alerts
|

Association between circulating microRNA-208a and severity of coronary heart disease

Abstract: Circulating microRNA (miR)-208a is specifically expressed in the heart muscle, which is involved in the regulation of myosin during cardiac development. Previous studies reported that cardiac-specific miR-208a level is significantly higher in plasma of coronary heart disease (CHD) patients. However, whether it correlates with severity of CHD, has never been elucidated before. The aim of this study was to explore the association between miR-208a and the presence and severity of CHD. Samples were collected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 23 publications
2
14
0
Order By: Relevance
“…The cDNA obtained was pre-amplified as described above for blood sample and amplified using the specific TaqMan micro-RNA assays (Life Technologies). 17 Primers for miR-19b were given as: forward, 5′-TGA TAA TTA GCA AGC AGG ATT A-3′ and reverse, 5′-ACC AAC ATT ACG CGG CAT CAT TA-3′. RNU6B was used as endogenous control.…”
Section: Quantitative Assessment Of Mirna-19bmentioning
confidence: 99%
“…The cDNA obtained was pre-amplified as described above for blood sample and amplified using the specific TaqMan micro-RNA assays (Life Technologies). 17 Primers for miR-19b were given as: forward, 5′-TGA TAA TTA GCA AGC AGG ATT A-3′ and reverse, 5′-ACC AAC ATT ACG CGG CAT CAT TA-3′. RNU6B was used as endogenous control.…”
Section: Quantitative Assessment Of Mirna-19bmentioning
confidence: 99%
“…In the present study we demonstrated that the human chronic indeterminate phase of Chagas disease results in increased levels of circulating miR-208a, an essential regulator of the genes involved in cardiac hypertrophy and fibrosis (Cunha-Neto et al, 2005 ; Wang et al, 2013 ; Doka et al, 2015 ; Shyu et al, 2015 ; Zhang et al, 2017 ). MiR-208a is encoded by an intronic region of the Myh6 gene that encodes α-myosin heavy chain, the prevalent heavy-chain contractile protein in the developed adult heart (Cunha-Neto et al, 2005 ).…”
Section: Discussionmentioning
confidence: 67%
“…MiR-208a is encoded by an intronic region of the Myh6 gene that encodes α-myosin heavy chain, the prevalent heavy-chain contractile protein in the developed adult heart (Cunha-Neto et al, 2005 ). Alterations in the miR-208a expression levels are frequently associated with pathological heart dysfunctions, such as hypertrophy, fibrosis, arrhythmias, contractile dysfunction and conduction abnormalities (Cunha-Neto et al, 2005 ; Wang et al, 2013 ; Doka et al, 2015 ; Shyu et al, 2015 ; Zhang et al, 2017 ). Indeed, overexpression of miR-208a is associated with coronary heart disease (Zhang et al, 2017 ), and its therapeutic inhibition leads to recovery of cardiac function during heart disease (Doka et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations